On The Geometric Continued Fractions in Positive Characteristic - Kthiri, Hassen; Driss, Sana (Journal of the Indonesian Mathematical Society, 2019)
In this paper we study another form in the field of formal power series over a finite field. If the continued fraction of a formal power seriesin $\mathbb{F}_q((X^{-1}))$ begins with sufficiently largegeometric blocks, then $f$ is transcendental.